Reconstruction formulas for photoacoustic imaging in attenuating media. (13th December 2017) - Scherzer, Otmar; Shi, Cong
Abstract: In this paper we study the problem of photoacoustic inversion in a weakly attenuating medium. We present explicit reconstruction formulas in such media and show that the inversion based on such formulas is moderately ill-posed. Moreover, we present a numerical algorithm for imaging and demonstrate in numerical experiments the feasibility of this approach.